2004
DOI: 10.1079/bjn20041131
|View full text |Cite
|
Sign up to set email alerts
|

The influence of different combinations of γ-linolenic acid, stearidonic acid and EPA on immune function in healthy young male subjects

Abstract: To determine the effects of EPA, stearidonic acid (STA) or g-linolenic acid (GLA) on immune outcomes, healthy male subjects consumed one of seven oil blends for 12 weeks. EPA consumption increased the EPA content of peripheral blood mononuclear cells (PBMC). Consumption of GLA (2·0 g/d) in the absence of STA or EPA increased di-homo-GLA content in PBMC. Neither STA nor its derivative 20 : 4n-3 appeared in PBMC when STA (, 1·0 g/d) was consumed. However, STA (1·0 g/d), in combination with GLA (0·9 g/d), increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
74
2
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 110 publications
(85 citation statements)
references
References 31 publications
5
74
2
2
Order By: Relevance
“…In studies where humans have increased their intake of SDA through supplementation, incorporation of SDA itself into blood lipids and cells has been very small but significant increases in EPA have been reported [97][98][99]. For example, Harris et al demonstrated that SDA modifies the ω-3 index (EPA+DHA in RBCs) with greater efficiency than ALA [103].…”
Section: 4mentioning
confidence: 99%
See 4 more Smart Citations
“…In studies where humans have increased their intake of SDA through supplementation, incorporation of SDA itself into blood lipids and cells has been very small but significant increases in EPA have been reported [97][98][99]. For example, Harris et al demonstrated that SDA modifies the ω-3 index (EPA+DHA in RBCs) with greater efficiency than ALA [103].…”
Section: 4mentioning
confidence: 99%
“…As explained above, the biosynthesis of longerchain ω-3 PUFAs from SDA is considered to be more efficient than from ALA due to it not requiring the rate limiting step catalysed by D6D and studies which have directly compared consumption of SDA to that of ALA have shown a greater increase of EPA in blood lipids and cells than seen for ALA consuming subjects, although no significant changes in plasma or red blood cell (RBC) DHA levels were observed [97][98][99][100].…”
Section: 4mentioning
confidence: 99%
See 3 more Smart Citations